Exp 86 Fairsite, Vancouver, B.C., Canada - Photo Graphics::::::::: (Agency Press)
The north shore of False Creek, as depicted in these photos, has transformed in four short years from an industrial area to a futuristic fairsite of Expo 86. The Stadium at B.C. Place, the world's largest air-supported building, and the geodesic Expo Centre will be landmarks in Vancouver for years to come.